Midwives’ approaches to early pushing urge in labour - Borrelli, Sara E.; Dattolo, Carmen; Nespoli, Antonella (Mark Allen Healthcare, 2015)
The objectives of this mixed-methods study were: a) to investigate midwives' approaches to early pushing urge (EPU); and b) to explore midwives' perspectives and experiences of helping women cope with EPU. A quantitative observational methodology was adopted to investigate midwives' approaches to EPU in 60 cases. A qualitative phenomenological approach was carried out in order to gain more in-depth understanding of midwives' views and experiences of EPU management strategies. It was found that midwives mainly adopt two approaches in the case of EPU: letting the woman do what she feels, and a stop-pushing technique. The findings are presented as four main domains: a) midwives' approaches to EPU; b) drivers guiding midwives' approaches to EPU; c) influencing factors in helping women cope with EPU; d) variation of midwives' approaches to EPU over time.